Breastfeeding as foodwork in the workplace among black, low-income women in South Africa - Farista, Feranaaz (School of Management Studies, 2023)
Return to work is cited as a key reason for women ceasing breastfeeding due to the conflict between the labour of bodywork required for jobs, and breastfeeding as a labour of foodwork. Through semi-structured, in-depth interviews with 33 black low-income mothers in Cape Town, South Africa, this study gives meaning to the labour of foodwork that these mothers perform. The data were analysed through an intersectional analytic lens to understand how race, class, and gender shape foodwork experiences. The study findings underscored the struggles, exacerbated by financial constraints, that low-income women endured balancing the demands of being a good mother and a good worker. Four key themes emerged that illustrate the compromised ability to enact foodwork: (1) foodwork experiences and precarity in the workplace, (2) structural inequalities and foodwork, (3) gender norms and social class: shaping child care and foodwork and, (4) local knowledges and foodwork. With these findings, recommendations for improving workplace support for low-income mothers foodwork activities are presented.